MOTIVATIONAL DYNAMICS AND DISCIPLINE WORKING IN THE ORGANIZATIONAL CULTURE OF GOVERNMENT AGENCIES: A CASE STUDY IN THE ESDM SERVICE IN BANTEN PROVINCE - Candra, Asep; Ginanjar, Egi; Mustofiyah, Ely; Humairoh, Yayu; Maliki, Budi Ilham (Yayasan Education and Social Center, 2024)
This study aims to understand the dynamics of motivation and work discipline in the context of organisational culture in the government environment, focusing on a case study at the Energy and Mineral Resources (ESDM) Service of Banten Province. The method used is qualitative, with data collection techniques through in-depth interviews, observations, and document studies. The study results indicate that the theories of Maslow, Herzberg, and Vroom influence employee work motivation by basic needs, recognition, and development opportunities. On the other hand, work discipline tends to be strong in administrative matters but is still weak in initiative and professional responsibility. A bureaucratic organisational culture also affects employee behaviour, strengthening compliance and limiting creativity. The conclusion of this study highlights the importance of work culture reform that supports performance-based rewards and strengthening proactive work values ​​to improve employee motivation and work discipline sustainably.